2011
DOI: 10.1177/1350650110397259
|View full text |Cite
|
Sign up to set email alerts
|

Piston skirt surface topography modelling during a low wear process

Abstract: Piston skirt surface topographies during a low wear process were analysed. The tendencies of parameter changes were studied. It was found that during the wear process one-directional random structures were superimposed on the machined piston skirt surface topographies. On the basis of this observation, a method of piston skirt surface topography modelling during engine operating was proposed. Piston skirt axial two-dimensional (2D) profiles and 3D surface topographies were simulated. The imposition of a comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…During mild wear, this surface became smoother with time [9]. Therefore, the imposition of smooth Gaussian surface topography on the machined surface seems to be a better solution than the truncation model [10][11][12][13][14][15][16][17]. The imposed surface is typically modeled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During mild wear, this surface became smoother with time [9]. Therefore, the imposition of smooth Gaussian surface topography on the machined surface seems to be a better solution than the truncation model [10][11][12][13][14][15][16][17]. The imposed surface is typically modeled.…”
Section: Introductionmentioning
confidence: 99%
“…The extension of this approach can be used when the number of processes is higher than two [14]. This method was used to simulate a low wear of the cylinder surface [15], of piston skirt surface [16], and of surface with isolated oil pockets [17]. In the last case, the modeled surfaces were correctly matched to the measured surfaces in 90% of analyzed cases.…”
Section: Introductionmentioning
confidence: 99%
“…30 Characterization of ST with frequency-representative Fourier transform was proposed with wavelet decomposition, 31 full frequency denoising technique based on wavelet decomposition, 32 autocorrelation approaches (e.g., autocorrelation function [AF]) 33 or Fourier reduction or random phase exclusion methods. 34 Many papers are referred to the cylinder liners and piston skirts assemblies 35,36 and assessments 37,38 Amplitude of NS (also referred to the measurement noise amplitude or shortly noise amplitude) can be directly specified by calculation of discrepancy from two measured details-results of two type of measuring with the same method. In other words, NS can be precisely defined by subtracting two results of measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers are referred to the cylinder liners and piston skirts assemblies 35,36 and assessments 37,38 of its surface qualities. Notwithstanding, the effect of both measurement frequency‐defined errors and procedures of its minimization on ST parameter calculation was not compressively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 27,28 developed a thermal model of mixed lubrication in point contact and showed that the non-Gaussian surface parameters have a large effect on the contact parameters. Krzyzak and Pawlus 29 analyzed piston skirt surface topographies during a low-wear process.…”
Section: Introductionmentioning
confidence: 99%